PENDUGAAN PRODUKTIVITAS POHON PAKAN ORANGUTAN SUMATERA (Pongo abelii) PADA KAWASAN PPOS (PUSAT PENGAMATAN ORANGUTAN SUMATERA), BUKIT LAWANG - Bungaran Bungaran; Pindi Patana; Erni Jumilaty (Program studi Kehutanan USU, 2015)
The population of Sumatran Orangutan (Pongo abelii) decreases due to forest conversion. In addition, the availability of feed orangutans also declining so much potential extinction of the Sumatran orangutan if this trend continues. This study aims to determine the productivity of the tree of the Sumatran orangutan (Pongo abelii) and ecological niche in the area of Sumatran Orangutan Observation Center (PPOS), Bukit Lawang. This study was conducted for 3 months observations performed every week. The result showed that the productivity of the tree of sumatran orangutan lowest for the urinary tree (Quercuss sumatrana) while the highest species productivity found in the forest of mango trees (Mangifera indica). Animal species found in the hills of mace, among others, sumatran orangutan, long-tailed monkeys, kedih, turtles, squirrels and hornbills.